Micro-optical elements for beam-shaping and optical manipulation : fabrication and experiments - Cheong, Wai Chye. (2008)
To date, the functional capabilities of micro-optical elements have only been demonstrated for micro-beam-shaping of novel beam modes. No optical manipulation experiment using novel beam modes generated by micro-optical elements has been reported. It is the objective of this thesis to validate the simplicity, robustness and usefulness of micro-optical elements for optical manipulation applications. In this work, 7 different novel micron-sized optical elements have been designed, fabricated and characterized for the micro-beam-shaping of novel beam modes in the application of optical manipulation. The novelty of this thesis includes the micro-beam-shaping of high quality Laguerre-Gaussian (or vortex) beam via micro-sized spiral-phase plate and kinofrom-spiral-phase plate designed for optical manipulation. The realization of the first-ever wavelength scalable wedge-phase plate and micro-double-axicon for the generation of vortex beam and self-imaged Bottle beam respectively is also presented. The generation of Bessel beam with long non-diffracting distance by fabricated micron-sized axicon is another cornerstone of this thesis. A simple and reliable single-step processing technique, using standard direct-write electron beam lithography technology, has been developed to realize the proposed micro-optical elements in SU-8 2000s resist. The averaged power conversion efficiency of fabricated elements is measured to be from ~ 75 % to > 90 %. This is at least a two fold increase when compared to conventional holograms (< 40 %). The application simplicity of the proposed elements has been validated through their successful integration onto an existing trapping system. No modification of apparatus or complex beam alignment is required. It is observed that the proposed elements are able to effect stable optical traps at a relative lower laser power due to their high power efficient nature. In this case, the transfer of orbital-angular-momentum onto trapped micro-particles by generated Laguerre-Gaussian beam is achieved with a 50 mW incident beam. The transverse trapping and levitation of micro-particles by generated Bessel beam is also realized with a much lower incident beam power of 80 mW and 150 mW respectively. Furthermore, the three-dimensional trapping of low-refractive index micro-particles by self-imaged Bottle beam is completed using a laser beam power of 100 mW. Such low level of trapping beam power has not been achieved by other reported works.